Microstructural and corrosion resistance characterisation of NiTi shape memory alloy modified at low-temperature plasma with carbon coatings produced via RFCVD and IBAD methods. (17th November 2019) - Witkowska, Justyna; Kamiński, Janusz; Płociński, Tomasz; Rajchel, Bogusław; Borowski, Tomasz; Wierzchoń, Tadeusz
ABSTRACT: NiTi shape memory alloy, both before and after low-temperature oxynitriding under glow discharge conditions combined with the production of a nano-sized outer carbon coating, was investigated. The study compares two types of carbon coatings: produced via the RFCVD (radio frequency chemical vapour deposition) and IBAD (ion beam-assisted deposition) methods. The latter was also enriched by randomly distributed silver nanoparticles. The study showed slight changes in roughness parameters and increased corrosion resistance after surface treatment processes. The largest impedance module and corrosion potential and the smallest density of corrosion current were achieved for samples with a carbon coating produced via the RFCVD process. The presented surface modifications using hybrid processes can extend the use of NiTi alloy in medicine due to the increased biocompatibility.